Vegetative Growth and Potential of Turi (Sesbania grandiflora) as Forage under PGPR Application on Ultisol Soil - Mardhiyetti; Sriagtula, Riesi; Sowmen, Simel; Aini, Qurrata; Martaguri, Imana (Andalasian Livestock, 2026)
Turi (Sesbania grandiflora) is a high-protein forage legume with significant potential to support ruminant nutrition in tropical regions. This study aimed to evaluate the effect of Plant Growth-Promoting Rhizobacteria (PGPR; Rhizomax) on the vegetative growth of turi as an indicator of forage productivity in ultisol soil. The experiment was conducted using a Completely Randomized Design with five treatments and five replicates: P0 (without PGPR), P1 (100 ml/plant), P2 (200 ml/plant), P3 (300 ml/plant), and P4 (400 ml/plant). The measured variables included plant height, stem diameter, and number of leaf stalks. Data were analyzed using analysis of variance (ANOVA), followed by Duncan’s Multiple Range Test when appropriate. The results showed that different doses of PGPR had no significant effect (P>0.05) on any of the observed parameters during the early vegetative phase. This indicates that PGPR application did not enhance the early growth performance or potential forage biomass production of turi under the conditions of this study. The lack of response is likely associated with the early growth stage, where external nutrient supplementation is not critical for plant development. These findings suggest that the effectiveness of PGPR on Turi as a forage crop may require longer observation periods or integration with additional nutrient sources to be fully realized.